A Recirculatory Model for Pharmacokinetics and the Effects on Bispectral Index After Intravenous Infusion of the Sedative and Anesthetic AZD3043 in Healthy Volunteers. (October 2015) - Björnsson, Marcus A.; Norberg, Åke; Kalman, Sigridur; Simonsson, Ulrika S. H.
Abstract : BACKGROUND: AZD3043 is a positive allosteric modulator of the γ-aminobutyric acid type A receptor, with sedative and anesthetic properties. We describe a population pharmacokinetic (PK) model of arterial and venous concentrations of AZD3043 and the pharmacodynamic effects on bispectral index (BIS) in healthy volunteers. METHODS: Arterial and venous plasma concentrations of AZD3043 and BIS were measured in 2 clinical studies in 125 healthy volunteers, where AZD3043 was given as a 1-minute bolus (1–6 mg/kg), a 30-minute infusion (1–81 mg/kg/h), or 0.8 + 10, 1 + 15, 3 + 30, and 4 + 40 (mg/kg bolus + mg/kg/h infusion for 30 minutes). Population PK/pharmacodynamic analysis was performed with NONMEM. RESULTS: A recirculatory model, comprising a series of 5 compartments for the transit of drug between venous and arterial plasma, 2 peripheral distribution compartments, and 1 compartment for the nondistributive transit of drug from arterial to venous plasma, described the PK of AZD3043. Systemic clearance was high (2.2 L/min; 95% confidence interval, 2.12–2.25), and apparent volumes of distribution were low, leading to a short elimination half-life. The apparent volumes of distribution of the arterial and peripheral compartments increased with increasing administered dose, giving a total apparent volume of distribution of 15 L after the lowest dose and 37 L after the greatest dose. A sigmoid maximum effect ( E max ) model with an EC 50 of 15.6 µg/mL and a γ of 1.7 described the relationship between AZD3043 effect-site concentrations and BIS. The between-subject variability in EC 50 was 37%. An effect compartment model, with a half-life of the equilibration rate constant ke0 of 1.1 min, described the delay in effect in relation to the arterial plasma concentrations. CONCLUSIONS: AZD3043 had a high clearance and a low apparent volume of distribution, leading to a short half-life. However, the apparent volume of distribution was dose dependent ( P < 0.001), leading to an increased half-life with increasing dose. The distribution to the effect site was fast and together with the short plasma half-life led to a fast onset and offset of effects. Abstract : Published ahead of print June 19, 2015